UHPLC-QTOFMS-Based Metabolomic Analysis of the Hippocampus in Hypoxia Preconditioned Mouse - Liao, Wen-Ting; Liu, Jie; Zhou, Si-Min; Xu, Gang; Gao, Yu-Qi; Liu, Wen-Yuan (Frontiers in Physiology, 2019)
Background: Hypoxia appears in a number of extreme environments, including high altitudes, the deep sea, and during aviation, and occurs in cancer, cardiovascular disease, respiratory failures and neurological disorders. Though it is well recognized that hypoxic preconditioning (HPC) exerts endogenous neuroprotective effect against severe hypoxia, the mediators and underlying molecular mechanism for the protective effect are still not fully understood. This study established a hippocampus metabolomics approach to explore the alterations associated with HPC. Methods: In this study, an animal model of HPC was established by exposing the adult BALB/c mice to acute repetitive hypoxia four times. Ultra-high liquid chromatography-quadrupole time-of-flight mass spectrometry (UHPLC-QTOFMS) in combination with univariate and multivariate statistical analyses was employed to deciphering metabolic changes associated with HPC in hippocampus tissue. MetaboAnalyst 3.0 was used to construct HPC related metabolic pathways. Results: The significant metabolic differences in hippocampus between the HPC groups and control were observed, indicating that HPC mouse model was successfully established and HPC could caused significant metabolic changes. Several key metabolic pathways were found to be acutely perturbed, including phenylalanine, tyrosine and tryptophan biosynthesis, taurine and hypotaurine metabolism, phenylalanine metabolism, glutathione metabolism, alanine, aspartate and glutamate metabolism, tyrosine metabolism, tryptophan metabolism, purine metabolism, citrate cycle, and glycerophospholipid metabolism. Conclusion: The results of the present study provided novel insights into the mechanisms involved in the acclimatization of organisms to hypoxia, and demonstrated the neuroprotective mechanism of HPC.